EVALUASI PENERAPAN PAJAK PENGHASILAN PASAL 21 MENURUT PMK NOMOR 262/PMK.03/2010 DAN PERATURAN DIRJEN PAJAK NOMOR 16/PJ/2016 PADA INSPEKTORAT DAERAH KABUPATEN MINAHASA SELATAN - Johannis, Lady M.; Sondakh, Jullie J.; Afandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
To establish an equal national development, funds are needed to be the financial resources. Income tax is acknowledged as one of the most potential financial resources. Tax is a contribution of assessable to the state without acquiring direct reciprocal services (contraprestation) and forceful under the law. Income tax section 21 is subjected to incomes for intance, salary, honorarium with different names associated to the employment, and individual services or positions. The purpose of this research is to evaluate whether the computation, deposit and report of Income Tax Section 21 at Regional Inspectorate of South Minahasa Regency are adequate according to conditions in PMK 262/PMK.03 Year 2010 and the Regulation of General Directorof Tax Number PER-16/PJ/2016. Analitycal method used in this study was descriptive method. According to the study finding, it can be concluded that the computation and deposit of Income Tax Section 21 implemented by the Regional Inspectorate of South Minahasa Regency is sufficient according to applied conditions in PMK 262/PMK.03 Year 2010. However, the Income Tax Section 21 report implemented by the Regional Inspectorate of South Minahasa Regency is unsatisfactory according to applied conditions in the Regulation of General Director of Tax Number PER-16/PJ/2016 because the expenditure treasurer did not report the Income Tax Section 21 closing.Keywords: income Tax Section 21, Computation System, Truncation System,Â  Deposit System and, Report System.